Gastroprotective Effect of Zingerone on Ethanol-Induced Gastric Ulcers in Rats - Sistani Karampour, Neda (Medicina (Kaunas), 2019)
Background and objectives: Zingerone is an ingredient of ginger (Zingiber officinale) with different pharmacological activities. Several studies have investigated the effect of zingerone on various gastrointestinal diseases, including irritable bowel syndrome and diarrhea. This study is aimed to evaluate the effect of zingerone on ethanol-induced gastric ulcers in rats. Materials and Methods: Gastric ulcers were induced by ethanol (96%, 5 mL/kg, po) in male wistar rats and zingerone (50, 100, and 200 mg/kg) was administrated orally. Normal saline and ranitidine were used as negative and positive control, respectively. In this study, the number and length of ulcers, and malondialdehyde (MDA) and nitric oxide (NO) levels in stomach tissues were determined. Results: The findings showed that the mean number and length of gastric ulcers were significantly lower in zingerone-received groups than ethanol group (P < 0.05). The level of malondialdehyde was decreased in the stomach of zingerone groups (P < 0.05) compared to the ethanol group. In addition, zingerone treatment prevented the decrease of nitric oxide level by ethanol in the stomach tissue. Conclusions: The present study showed that zingerone has a protective effect on the ethanol-induced gastric ulcer, which may be due to its free radical scavenging activity.